Professional Training, Personality, and Financial Rewards Shaping Students' Career Interest as Public Accountants: Pelatihan Profesional, Personalitas, dan Penghargaan Finansial dalam Pembentukan Minat Karir Akuntan Publik - Novayoka, Rama; Rahayu, Duwi (Indonesian Journal of Law and Economics Review, 2024)
The general background of this study is rooted in the importance of identifying factors that drive accounting students' interest in becoming public accountants. The specific background focuses on professional training, personality traits, financial rewards, and job market considerations as potential influencers of career interest. While prior studies have explored career selection, there remains a knowledge gap in understanding how these factors interrelate in the context of public accounting careers. This study aims to examine the effects of professional training, personality, financial rewards, and job market considerations on accounting students' career interest. Using a quantitative approach, data was collected from 100 fifth-semester accounting students at Muhammadiyah University of Sidoarjo through purposive sampling. The results show that professional training, financial rewards, and job market considerations each have a positive and significant effect on students' interest in a public accounting career. The novelty of this study lies in its integrated analysis of these variables, providing insights for educators and policymakers. The implications suggest the need for academic programs to enhance professional training, clarify financial incentives, and provide information on job market trends to support students’ career decisions. Highlights: Professional training significantly influences students' interest in public accounting careers. Financial rewards play a key role in motivating students to pursue public accounting. Job market considerations positively affect students' career choices in accounting. Keywords: Student Interest, Public Accountant, Professional Training, Personality, Financial Rewards